The Ethics and Economics of Patenting the Human Genome - Flowers, Edward B. (Journal of business ethics, 1998)
This paper attempts to better define the areas of conflict and agreement between value ethics and the theoretical ethics of the market processes at work in the biotechnology industry. Despite the apparent lack of ethics in an oligopolistically competitive pharmaceuticals industry, the paper concludes that the current stage of development of the medical biotechnology subindustry offers unparalleled opportunities for ethical systems to influence the market-based development of biotechnology. Ethical conversations between doctors and biologists with ethicists can help the market absorb more of the reflective wisdom that ethics brings when discussing such issue areas as justice, patents of the human genome, and modifications of the human genome. If conversations between ethicists and biotechnological managers and doctors are successful the metaphors of market-based financing may be refined and the knowledge base of the good increased.